'NOT KNOWING IS MOST INTIMATE': KOAN PRACTICE AND THE FOG OF WAR. Issue 1 (3rd July 2021) - Trew, Noel Maurer
ABSTRACT: The branch of international humanitarian law (IHL) pertaining to targeting is notoriously challenging for decision makers to apply in practice. The rules of distinction, precautions and proportionality in attack form the bedrock of targeting law, but compliance with these rules requires combatants to correctly understand what is happening in the battlespace. Those who decide upon, plan or execute an attack may not always have access to the right kind or amount of information needed to correctly set up an attack. Furthermore, they may not even know what information they need. Given the ambiguity posed by inadequate intelligence or information overload, how can combatants train themselves to successfully cut through the fog of war? In Japanese Zen (Chinese: Chan ) Buddhism, adherents typically practice meditation methods featuring elements of open monitoring and focused attention. One style of focused attention, known as kōan practice, is often used by those in the Rinzai and (to a lesser extent) Sōtō schools of Zen. Kōans are short stories that Zen teachers use to communicate those Buddhist insights that cannot be expressed through direct communication, such as the experience of 'nonduality'. Although kōans are often described as riddles or puzzles, they are not intended to be solved logically. Rather, the practitioner focuses their attention upon the kōan and observes what happens when linguistic and logical means of 'solving' it fall away. By training the mind to recognise its attachments to particular concepts or habitual ways of problem-solving, those who take up this practice in its proper context may find themselves better prepared to make decisions based on ambiguous information, and to spot errors in their perception or thinking when considering such matters of grave importance.